2010
DOI: 10.1002/ijc.25499
|View full text |Cite
|
Sign up to set email alerts
|

Sodium dichloroacetate selectively targets cells with defects in the mitochondrial ETC

Abstract: The “Warburg effect,” also termed aerobic glycolysis, describes the increased reliance of cancer cells on glycolysis for ATP production, even in the presence of oxygen. Consequently, there is continued interest in inhibitors of glycolysis as cancer therapeutics. One example is dichloroacetate (DCA), a pyruvate mimetic that stimulates oxidative phosphorylation through inhibition of pyruvate dehydrogenase kinase. In this study, the mechanistic basis for DCA anti‐cancer activity was re‐evaluated in vitro using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
152
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(183 citation statements)
references
References 41 publications
21
152
0
Order By: Relevance
“…21 This dual-targeting strategy is also supported by studies showing DCA to be more effective against cancer cells with mitochondrial defects, such as rho(0) MCF7 cells, 25 mitochondrial ND2 mutant cells 26 and oligomycin-treated HCT116 colon cancer cells. 18 However, the precise mechanism by which DCA enhances cytotoxicity is not always clear.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 This dual-targeting strategy is also supported by studies showing DCA to be more effective against cancer cells with mitochondrial defects, such as rho(0) MCF7 cells, 25 mitochondrial ND2 mutant cells 26 and oligomycin-treated HCT116 colon cancer cells. 18 However, the precise mechanism by which DCA enhances cytotoxicity is not always clear.…”
Section: Discussionmentioning
confidence: 92%
“…Mitochondrial changes may be involved in DCA sensitization of cancer cells toward apoptosis. It has been previously reported that DCA can depolarize the mitochondrial membrane potential (MMP), 7,25 which has been postulated to sensitize cancer cells toward apoptosis. 37 Using JC-1 staining to measure the MMP, it was found that JC-1 red staining decreased from as early as 3 hr post-DCA treatment in T-47D cells (Fig.…”
Section: Dca Can Sensitize Cancer Cells Toward Apoptosis Via Off-targmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that by inducing a metabolic change from fermentation to OXPHOS, DCA specifically induces apoptosis in tumor cells. DCA has clinical benefits for the treatment of certain cancer patients (Flavin, 2010,Michelakis et al, 2010, although its use is under debate (Stockwin et al, 2010,Heshe et al, 2011. In view of our results (Charni et al, 2010), it should be interesting to investigate the clinical association of DCA with CTL-mediated immunotherapy because DCAinduced MHC-I expression should facilitate plasma membrane expression of TAAs allowing proper recognition by CTLs.…”
Section: Avoiding the Immune Attackmentioning
confidence: 86%
“…However, many studies have raised doubts regarding the anti-cancer activity of DCA as a potential metabolism-targeting therapy (Michelakis et al, 2008). The controversy has focused on two issues: inconsistency in anti-cancer activity between in vitro and in vivo studies (Papandreou et al, 2011) and the effectiveness of the DCA administration method (Stockwin et al, 2010;Sun et al, 2010). The opposing findings have mainly arisen from the most studied colorectal cancer model.…”
Section: Introductionmentioning
confidence: 99%